2012
DOI: 10.1097/prs.0b013e31824ecd77
|View full text |Cite
|
Sign up to set email alerts
|

The Tear Trough Ligament

Abstract: This study clearly demonstrated that the prominence of the tear trough has its anatomical origin in the tear trough ligament. This ligament has not been isolated previously using standard dissection, but using the approach described, the tear trough ligament is clearly seen. The description of this ligament sheds new light on considerations when designing procedures to address the tear trough and the midcheek.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(82 citation statements)
references
References 24 publications
1
80
0
1
Order By: Relevance
“…The few anatomical studies in fresh cadaver dissections revealed that the main problem is subcutaneous fat [16][17][18][19] . The existence of a ligament was in doubt [21] . Our dissections proved that the attachment is of muscle origin [22] and not a specific ligament.…”
Section: Discussionmentioning
confidence: 99%
“…The few anatomical studies in fresh cadaver dissections revealed that the main problem is subcutaneous fat [16][17][18][19] . The existence of a ligament was in doubt [21] . Our dissections proved that the attachment is of muscle origin [22] and not a specific ligament.…”
Section: Discussionmentioning
confidence: 99%
“…This fat is separated by the superfi cial lamina of the deep temporal fascia (layer 5) from the fat within the prezygomatic space (layer 6) overlying the periosteum (layer 7) [52][53][54] . The inferior boundary of both the SOOF and of the prezygomatic space is the zygomatico-cutaneous ligament and the superior boundary is the bilaminar orbicularis retaining ligament (Table 3 ) [ 55 ] . The SOOF is connected via the temporal tunnel to the lower temporal compartment, since both are located in layer 4 and reside on top of the superfi cial lamina of the deep temporal fascia [ 44 ] .…”
Section: Infraorbital Region: Tear Trough and Sub-orbicularis Oculi Fmentioning
confidence: 99%
“…Dieses Fettkompartiment wird vom oberflächlichen Blatt der Fascia temporalis profunda (Schicht 5) vom Fettkompartiment im präzygomatischen Raum (Schicht 6) getrennt, der dem Periost aufliegt (Schicht 7) . Die untere Grenze sowohl des SOOF als auch des präzygomatischen Raums ist das Ligamentum zygomatico‐cutaneum und die obere ist das bilaminäre Rückhalteband des M. orbicularis oculi (orbicularis‐retaining ligament) (Tabelle ) . Das SOOF ist über den temporalen Tunnel mit dem unteren temporalen Kompartiment verbunden, da sich beide in Schicht 4 befinden und über dem oberflächlichen Blatt der Fascia temporalis profunda liegen .…”
Section: Infraorbitale Region: Tränensäcke Und Soof (Suborbicularis Ounclassified